The missing base molecules in atmospheric acid–base nucleation. Issue 10 (25th July 2022) - Cai, Runlong; Yin, Rujing; Yan, Chao; Yang, Dongsen; Deng, Chenjuan; Dada, Lubna; Kangasluoma, Juha; Kontkanen, Jenni; Halonen, Roope; Ma, Yan; Zhang, Xiuhui; Paasonen, Pauli; et al.
Abstract: Transformation of low-volatility gaseous precursors to new particles affects aerosol number concentration, cloud formation and hence the climate. The clustering of acid and base molecules is a major mechanism driving fast nucleation and initial growth of new particles in the atmosphere. However, the acid–base cluster composition, measured using state-of-the-art mass spectrometers, cannot explain the measured high formation rate of new particles. Here we present strong evidence for the existence of base molecules such as amines in the smallest atmospheric sulfuric acid clusters prior to their detection by mass spectrometers. We demonstrate that forming (H2 SO4 )1 (amine)1 is the rate-limiting step in atmospheric H2 SO4 -amine nucleation and the uptake of (H2 SO4 )1 (amine)1 is a major pathway for the initial growth of H2 SO4 clusters. The proposed mechanism is very consistent with measured new particle formation in urban Beijing, in which dimethylamine is the key base for H2 SO4 nucleation while other bases such as ammonia may contribute to the growth of larger clusters. Our findings further underline the fact that strong amines, even at low concentrations and when undetected in the smallest clusters, can be crucial to particle formation in the planetary boundary layer. Abstract : Forming an (H2 SO4 )1 (amine)1 cluster is the rate-limiting step in atmospheric H2 SO4 -amine nucleation, which governs the fast formation of new particles from gaseous precursors.